PSYCHOLOGICAL WELL-BEING OF DISABILITY EMPLOYMENTS - Putri Deviyeni; Zamralita Zamralita; Daniel Lie (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2023)
There are 22.5 people with disabilities in Indonesia, but in 2021 the number of people with disabilities who are in employment will be 5.37% or 7.04 million people of the total number of workers in Indonesia. Employees with disabilities have different characteristics from employees in general. Psychological well-being for employees is a view of support received, accessibility and equality in work environment, social support from colleagues, as well as better opportunities for self-development. There were 81 participants in this study. The criteria for participation were employees with disabilities, employees working at PT. X, employees with at least SLB/SMK/SMA/equivalent education and employees who had worked at the company for at least one year. The measurement instrument used in this study is psychological well-being scale (PWBS), which is based on Ryff's dimensions of psychological well-being. It has a total of 45 statement items. The results of the normality test show that the research data have a normal distribution. The research result shows a high level of psychological well-being (M=4.03) with dimensions of variable autonomy (M=3.87), environmental mastery (M=3.95), personal growth (M=4.10), positive relationship with others (M=4.07), life purpose (M=4.06) and self-acceptance (M=4.06). This research found no differences in psychological well-being based on gender, age, tenure and disability categories, but significant differences based on education level, employment status and marital status using the independent samples t-test dan ANOVA.